Strong tolerance of blue-green alga Microcystis flos-aquae to very high pressure. (September 2015) - Ono, F.; Nishihira, N.; Hada, Y.; Mori, Y.; Takarabe, K.; Saigusa, M.; Matsushima, Y.; Yamazaki, D.; Ito, E.
Abstract: It was shown in our previous reports that a few spores of moss Venturiella could tolerate the very high pressure of 20 GPa for 30 min and germinated a protonema to the length of 30 μm. However, these spores did not grow any further, and disappeared at around 30 days of incubation after seeded. On the other hand, colonies of blue-green alga Microcystis flos-aquae came to appear about 76 days after the moss spores were seeded. Many of these colonies appeared at the places where the moss spores had disappeared. These colonies were formed by the algae that had adhered to the spore cases of the moss and survived after exposure to the very high pressure of 20 GPa. Though the appearance of the colonies of high pressure exposed algae was delayed by about 50 days compared with that of the control group which was not exposed to high pressure, there seems no difference in their shape and color from those of the control group. The pressure tolerance of blue-green alga is found to be enormously strong, and it can survive after exposure to the high pressure which corresponds to the depth of about 550–600 km from the surface of the Earth, just above the lower mantle. Highlights: We exposed blue-green algae to ultra-high pressure of 20 GPa for 30 min. The algae could tolerate to the ultra-high pressure. The appearance of the colonies of algae delayed by 50 days compared with control. The pressure corresponds to the depth of 550–600 km from the earth׳s surface.